Validity and reliability of a specific anaerobic test for mixed martial arts - Andrade, V. L. [UNESP]; Foresti, Y. F.; Almeida, P. B. [UNESP]; Araujo, M. Y.C. [UNESP]; Kalva-Filho, C. A. [UNESP]; Papoti, M. [UNESP] (Elsevier, 2022)
Objectives: The present study aimed to verify the reproducibility and validity of a specific assessment for Mixed Martial Arts athletes. Equipment and methods: Twelve male Mixed Martial Arts athletes, participated in this study. They underwent a test and re-test for an anaerobic specific assessment for Mixed Martial Arts athletes, a graded incremental test, ten submaximal efforts, and a supramaximal effort to determine the Maximal Accumulated Oxygen Deficit. Also, they performed the Wingate test for upper limbs and for lower limbs to assess the anaerobic power. Results: The Mixed Martial Arts test showed reliability; the total of strikes, and strikes in bouts 1, 2 and 3, showed values of ICC between 0.50–0.70; coefficient of variation between 3.1–4.3%. A strong correlation was found among the number of total strikes and the Maximal Accumulated Oxygen Deficit (test r = 0.87; re-test r = 0.96), evidencing the importance of anaerobic capacity during the test. Besides, was found a moderate correlation between the total of strikes and aerobic power (test r = 0.67; re-rest r = 0.60), showing the high aerobic contribution during the trial. We concluded that the specific test for Mixed Martial Arts is reliable and valid for assessing anaerobic capacity.
Validité et fiabilité d'un test anaérobie spécifique pour les arts martiaux mixtes
Keywords: Anaerobic; Assessment-protocol; MAOD; MMA; Wingate